MSMEs Empowerment in Maintaining the Economic Stability of Village Communities: A Case Study in Lebak Regency, Banten Province - Rahayu, Neneng Sri; Priyono, Budi; Rizki, Muhammad; Kurniawan, Yoel Adi (KnE Social Sciences, 2025)
MSME empowerment is organized as an integral part of national economic development to realize the prosperity of the people. Muncang District of Lebak Regency, being an underdeveloped village, has the potential for MSMEs that can support the economy of its community, including processing agricultural products such as bananas and cassava, handicrafts such as stick plates, and small industries, such as tempeh. This research aims to explore the MSME empowerment strategy in Muncang District. It uses a qualitative method and descriptive approach with primary data collection techniques such as interviews, observations, and focus group discussions. The local government has encouraged villages to include MSME development programs through Village Revenue and Expenditure Budget (APBDes) and various kinds of training programs and issuing business legality. MSMEs in Muncang district have considerable potential through the processing of agricultural products and handicrafts. Although they still lack confidence in developing their businesses, MSME players have the desire to grow. There needs to be collaboration from various parties so that MSMEs in Muncang district can grow rapidly and contribute to the improvement of the regional economy. The local government also needs to strengthen mentoring and training for MSME players to improve knowledge, skills, and business management, as well as facilitate MSMEs’ access to capital, which will indirectly maintain the stability of the village economy.